Foreign Direct Investment Role on Poverty Reduction in 33 Provinces in Indonesia - Suryatno Wiganepdo S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to find out the role of foreign investment in poverty rates in all provinces in Indonesia. This research uses quantitative methods by utilizing data released by the Central Bureau of Statistics, Bank Indonesia and the Ministry of Manpower and Transmigration. The analysis uses the least square panel method by conducting a combination analysis of time series data and cross section data by taking samples in 33 provinces in Indonesia. The results of the study proved that when there was an increase in foreign capital growth in 33 provinces in Indonesia, the poverty rate in most of the provinces that are being studied are decreasing. Foreign Direct Investment has positive impact in decreasing the poverty rates in Indonesia. Indonesian government need to facilitate and support the positive foreign investment environment in all provinces in Indonesia